The creation of Kazakh national identity - Shlapentokh, Dmitry, author.
1 online resource
Keywords: "This monograph utilizes three theoretical models to explain Kazakhstan's emergence as an independent state and its changing relationships with the broader world, particularly Russia, since the beginning of the twentieth century. The compelling approach to Kazakhstan's history will appeal to postgraduate students and scholars in Russian history and world history"--